Food waste in time of COVID-19: The heterogeneous effects on consumer groups in Italy and the Netherlands. (1st January 2023) - Masotti, Matteo; van der Haar, Sandra; Janssen, Anke; Iori, Elisa; Zeinstra, Gertrude; Bos-Brouwers, Hilke; Vittuari, Matteo
Abstract: Since COVID-19 outbreak, States adopted different combinations of measures to restrain its spread that affected individual behaviors and the already fragile local and global food systems. The aim of this research is to contribute to the scientific debate around food systems sustainability through the analysis of behavioral shifts in household food waste drivers, specifically occurring during the recent global pandemic. A survey was developed based on an extended version of the Motivation-Opportunity-Ability (MOA) approach. A representative sample of 3000 respondents in Italy and in the Netherlands (1500 per country) completed this survey in May 2020, while lockdown to mitigate the first wave of COVID-19 outbreak was active in both countries. A cluster analysis based on individual food-waste- related behaviors identified four homogenous groups of consumers in the Italian sample and five in the Dutch sample. The comparative analysis of these groups led to the identification of several communalities in behavioral patterns, both within and between the two countries. Results suggest that in both countries, self-reported quantities of household food waste actually decreased, with a stronger reduction reported by Italian consumers. The MOA approach allowed to explain this perceived reduction as largely depending on the increase of opportunity to dedicate more time - to food-related activities as compared to the pre-COVID-19 period, with positive consequences on food management ability. These findings assist in drafting recommendations for tailored interventions to reduce the amount of domestic food waste and preserve positive behaviors emerged during lockdown, that could be continued in the absence of crisis.